2020
DOI: 10.3390/ijms21207517
|View full text |Cite
|
Sign up to set email alerts
|

GPR4 Knockout Improves the Neurotoxin-Induced, Caspase-Dependent Mitochondrial Apoptosis of the Dopaminergic Neuronal Cell

Abstract: In Parkinson’s disease, mitochondrial oxidative stress-mediated apoptosis is a major cause of dopaminergic neuronal loss in the substantia nigra (SN). G protein-coupled receptor 4 (GPR4), previously recognised as an orphan G protein coupled-receptor (GPCR), has recently been claimed as a member of the group of proton-activated GPCRs. Its activity in neuronal apoptosis, however, remains undefined. In this study, we investigated the role of GPR4 in the 1-methyl-4-phenylpyridinium ion (MPP+) and hydrogen peroxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
3
14
1
Order By: Relevance
“…Which demonstrate the pharmacological inhibition of GPR4 prevents the MPTP induced mitochondrial oxidative stress and prevent the caspase 3 dependent apoptotic cell death. This result is equivocal with our previously published in vitro data using both genetic and pharmacological inhibition of GPR4 in the human dopaminergic neuronal cell [22].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Which demonstrate the pharmacological inhibition of GPR4 prevents the MPTP induced mitochondrial oxidative stress and prevent the caspase 3 dependent apoptotic cell death. This result is equivocal with our previously published in vitro data using both genetic and pharmacological inhibition of GPR4 in the human dopaminergic neuronal cell [22].…”
Section: Discussioncontrasting
confidence: 99%
“…We have shown the GPR4 is activate in the physiological pH (supplement data S1) and capable of potentiating the effect of MPP + , an active metabolite of MPTP [22]. Here we intended to find out if MPTP treatment has any effect on GPR4 expression level over time in cerebellum, cerebral cortex, substantia nigra, hippocampus, pons medulla, mid brain and striatum of mice brain after 1, 3 and 7 days of last MPTP injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings demonstrate that the pharmacological inhibition of GPR4 prevented MPTP-induced mitochondrial oxidative stress and prevented the initiation of the caspase 3-dependent apoptotic cell death pathway. This result aligns with our previously published in vitro data that examined both the genetic and pharmacological inhibition of GPR4 in a human dopaminergic cell line [22].…”
Section: Discussionsupporting
confidence: 92%
“…However, no study has examined the role played by GPR4 in the apoptotic neuronal cell death associated with neurodegenerative disease. We were the first to investigate the effects of GPR4 knockout and overexpression in dopaminergic neuronal cells [ 22 ]. Our previous study showed that GPR4 knockout or pharmacological inhibition reduced neurotoxin-induced caspase 3-dependent apoptotic cell death.…”
Section: Introductionmentioning
confidence: 99%